An Out Come of Transvaginal Repair in 50 Cases of Vesico-Vaginal Fistula (Medical Forum Monthly, 2024)
ABSTRACTObjective: To see the out come of transvaginal repair of vesico-vaginal fistula.Study Design: A consecutive case series study.Place and Duration of Study: This study was conducted in the department of Urology and Dialysis Unit Peoples Medical College Nawab Shah, from Jan 2007 to the Dec 2009.Materials and Methods: Patients were collected from the urology out patient department and the department of gynecology People’s Medical College Nawab shah. Total 50 females were operated for the vesico-vaginal fistula trans-vaginally. After the admission care full history and examination were done to demonstrate the incontinence subjectively and objectively. Before surgery all subjects were diagnosed by the cystoscpic examination. All subjects were operated transvaginally.Results: The total 50 females were operated for the vesico-vaginal fistula trans-vaginally. In 35 cases obstructed & prolonged labour and in 15 cases pelvic surgery was the cause of vesico-vaginal fistula. Cystoscopically all fifty fistulae were divided according to their site in the bladder. Supra trigonal 07, trigonal 35 and Marginal 08. All were repaired transvaginally. After two weeks catheter was removed, the leakage occurs in four (04) cases in supra-trigonal cases. In trigonal variety of vesico-vaginal fistula all thirty five (35) cases only three (03) fistulae were leaked. In third variety of vesico-vaginal fistula was marginal variety. Total eight (08) fistulae were and three (03) out of eight fistulae were leaked.Conclusion: We conclude that transvaginal is an excellent approach for the vesico-vaginal fistula, especially in trigonal, solitary and smaller i.e. <4cm variety of fistulae. Careful selection of the patient and the time of repair are the important mile stones for the successful out come.